Manajemen dan Kepemimpinan Kepala Sekolah yang Efektif - Sugeng Utomo (Jurnal Aplikasi Manajemen, 2010)
The purpose of this research is to describe the substance the effective principal’s management to increase the quality of public elementary school/MI (Islamic elementary school) in Malang and the effective principal’s leadership to increase the quality of public elementary school/MI in Malang. This research was conducted by using multi cases qualitative research approach in three super elementary schools in Malang, those are MIN Malang 1, SDN Kauman I and SDN Madyopuro IV. Data was collected by observation, interviews, and documentation. The collected data was analyzed descriptively by: (a) data reduction, (d) data presentation, (c) drawing conclusion, (d) individual data analysis, (e) cross cases data analysis. Data analysis was conducted through case data analysis and continued by with cross cases analysis. Research finding shows that the substance of effective management in three super elementary schools/MI in Malang (a) studentship management; (b) curriculum management; (c) human resources management; (d) tools and equipments management, (e) human relation management in which all of the managed professionally. The effective principal’s leadership refers to vision, mission, and objectives of SD/MI by implementing the establishing, empowering to teachers and staffs as well as students.Keywords: management, leadership, principal, effective.